Effects of Comorbidities on Pain and Function After Total Hip Arthroplasty - Lan, Pingwen; Chen, Xi; Fang, Zhi; Zhang, Jianjun; Liu, Shuping; Liu, Yuehong (Frontiers in Surgery, 2022)
Background: The growing number of patients undergoing total hip arthroplasty (THA) and postoperative outcomes receive increasing attention from doctors and patients. This study aimed to elucidate the effects of comorbidities on postoperative function, pain, complications, readmission rate, and mortality. Methods: We included consecutive patients who underwent initial unilateral THA between 2017 and 2019. The Charlson comorbidity index (CCI) and the WOMAC and SF-36 (physical function, body pain) scales were assessed preoperatively and at 3, 6, 12, and 24 months postoperatively. The complications, 30-day readmission, and mortality rates assessed the impact of comorbidities and their changes over time on the WOMAC and SF-36 scores during follow-up. We used mixed model linear regression to examine the association of worsening comorbidity post-THA with change in WOMAC and SF-36 scores in the subsequent follow-up periods, controlling for age, length of follow-up, and repeated observations. Results: This study included 468 patients, divided into four groups based on comorbidity burden (CCI-0, 1, 2, and ≥3). The physiological function recovery and pain scores in the CCI ≥ 3 group were inferior to the other groups and took longer than the other groups (6 vs. 3 months) to reach their best level. The four groups preoperative waiting times were 2.41±0.74, 2.97±0.65, 3.80±0.53, and 5.01±0.71 days, respectively. The complications, 30-day readmission, and 1-year mortality rates for the overall and the CCI ≥ 3 group were 1.92% and 4.69%, 0.85% and 2.01%, and 0.43% and 1.34%, respectively, with no mortality in the other groups . Conclusion: Patients with higher CCI were more susceptible to physical function and pain outcome deterioration, experienced longer waiting time before surgery, took longer to recover, and had higher rates of complications, 30-day readmission, and mortality after THA. Older age in the group led to a greater impact.